Research on the Peak Carbon Dioxide Emission Strategy of Chinese Port Based on Carbon Emission Estimation - Fan, Shenghai; Lu, Ziai (Frontiers in Environmental Science, 2022)
Port is an important node of a country's external goods circulation, as well as a large consumer of energy consumption. With the aggravation of climate change and the attention of the international community, the Chinese government has set a differentiated peak industry target. Therefore, the study of port carbon emissions is of great significance to evaluate whether China can achieve the peak industry target. This paper uses STIRPAT model to study the trend of carbon emissions under different scenarios based on the energy consumption data of Chinese ports from 2010 to 2019, and analyzes the possibility of the peak carbon dioxide emission of Chinese ports. The results show that the carbon emissions of Chinese ports have peaked in 2014 under most scenarios, with CO2 emission of 9,213,500 tons and carbon emission intensity of 0.783 tons of CO2 /103-tons of throughput. In addition, considering other scenarios, carbon emission action strategies should be formulated according to the differences of carbon emission peaking conditions of specific ports.